Russian-Jewish Intellectuals outside the Pale of Settlement at the Beginning of 20th Century: in Search of Identity (Doctor I. Ya. Meerovich in Yekaterinodar) - E. S. Norkina (Научный диалог)
The process of formation of the Russian-Jewish intellectuals of the early twentieth century on the example of the biography of the doctor I. Ya. Meerovich is illustrated in the article. The author of the article notes that Meerovich, having passed the path of “selective integration”, firmly entered Russian society, moving away from the traditional Jewish way of life. It was revealed that, being in close contact with the Russian environment, he continued to maintain contact with the Jewish community. The author concludes that the determining factor for the Russian-Jewish intellectuals is a sense of the strength of their position in society and the maintenance of good neighborly relations with the surrounding community. It is shown that representatives of the Russian-Jewish intellectuals felt themselves involved at the same time in two cultural societies - Russian and Jewish, and this feeling was the key. The research sources were both published and unpublished materials from the collections of Russian and foreign archives: Meerovich’s correspondence, periodicals, journalism, court documents, declassified intelligence information of the Ministry of Internal Affairs.